Metagenomic and metabolomic analyses show correlations between intestinal microbiome diversity and microbiome metabolites in ob/ob and ApoE−/− mice - Dong, Sashuang; Wu, Chengwei; He, Wencan; Zhong, Ruimin; Deng, Jing; Tao, Ye; Zha, Furong; Liao, Zhenlin; Fang, Xiang; Wei, Hong (Frontiers in Nutrition, 2022)
Obesity and atherosclerosis are the most prevalent metabolic diseases. The ob/ob and ApoE-/- mice are widely used as models to study the pathogenesis of these diseases. However, it’s unclear how gut microbes, gut bacteriophages and metabolites change in these two disease models. In this study, wild-type C57BL/6J(Wt) mice as normal control group, the intestinal archaea, bacteria, bacteriophages and microbial metabolites of ob/ob and ApoE-/- mice were analyzed by metagenome and metabolome. The analysis of intestinal archaea showed that the abundances of Methanobrevibacter, Methanobrevibacter and Halolamina in ob/ob group were significantly increased and decreased, respectively, compared with those in Wt and ApoE-/- groups (p < 0.05). At the bacterial genus level, compared with Wt group, the relative abundance of Enterorhabdus, Alistipes, Bacteroides, Prevotella, Rikenella, Barnesiella, Porphyromonas, Riemerella and Bifidobacterium were significantly decreased (p<0.05) in ob/ob mice and the relative abundance of Akkermansia was significantly decreased in ApoE-/- group. What’s more, in comparison to Wt group, the relative abundance of A. muciniphila and L. murinus were significantly decreased and increased (p<0.05) in ob/ob and ApoE-/- groups, respectively. Lactobacillus_ prophage_ Lj965 and Lactobacillus _ prophage _ Lj771 were significantly more than that in ob/ob mice compared to Wt mice. Comparing the Aminoacyl-tRNA biosynthesis metabolic pathway in ob/ob and ApoE-/- mice, we found that the enriched compounds including Phenylalanine, Glutamine, Glycine, Serine, Methionine, Valine, Alanine, Lysine, Isoleucine, Leucine, Threonine, Tryptophan and Tyrosine were down-regulated in ApoE-/- mice. As Aminoacyl-tRNA synthetases (ARSs) is considered manifestation of metabolic diseases, and is closely associated with obesity, atherosclerosis and type 2 diabetes.These basic data offer new insights into our understanding of the possible causes behind the diseases and and laid a foundation for studying the regulation of different food nutrients on metabolic disease models.